Становлення трудового законодавства України у сфері правового регулювання дисциплінарної відповідальності - Подорожній, А. Ю.; Podorozhnii, A. Yu.; Артем Подорожній (Наше право. - 2022. - № 3. - С. 158-164, 2022)
Здійснено комплексний історико-правовий аналіз становлення трудового законодавства України у сфері правового регулювання дисциплінарної відповідальності. Розглянуто нормативно-правові акти, які діяли у різні історичні періоди та регулювали питання дисциплінарної відповідальності працівників. Виокремлено чотири ключові етапи розвитку системи правового регулювання відповідного правового інституту. Акцентовано увагу на тому, що на сьогодні розвиток трудового законодавства, норми якого спрямовані на регулювання дисциплінарної відповідальності, не є завершеним, а відтак це питання є перспективним напрямом наукових пошуків.

It is argued that in order for the norms of labor legislation in the fi eld of disciplinary responsibility to correspond to the level of development of social and market relations in society, it is necessary to conduct research in its historical and legal aspect, which is necessary for the positive experience of past years to be properly refl ected in legislation of modern Ukraine. It was established that the fi rst signs of disciplinary responsibility were found on the territory of Ukraine in the XVII-XVIII centuries. during the time of the hetmanship, but the content of this institute did not correspond to today’s idea of the order of its application and the level of severity of the penalties applied. Therefore, the range of subjects to whom the measures of disciplinary infl uence established at that time were applied was limited only to employees, with the simultaneous equating of their illegal actions to crimes, with the subsequent application of criminal means of infl uence to the guilty. It was found that the period from the beginning of the 19th to the beginning of the 20th century (until 1917) was decisive for the formation of responsibility in domestic labor law and this fi eld in general, since at that time there was a gradual departure from ensuring labor discipline by criminal legal means with simultaneous increasing the role and effect of norms of civil and labor law. The legal features of labor responsibility began to take shape, with the appearance of signs, albeit vague, between disciplinary and material responsibility. Attention is drawn to the fact that in the period from the October Revolution to the Great Patriotic War (during the period of the fi rst Labor Code of the beginning of the 20th century), the Codes of Labor Laws of 1918 and 1922 refl ected the state policy in the fi eld of labor relations regulation, when criminal liability was again applied in the form of disciplinary sanctions, at the same time, other measures of disciplinary infl uence were already applied. In this historical period, brutal methods of strengthening labor discipline were used, as well as strict measures of disciplinary responsibility. It was found out that from the end of the 80s and the beginning of the 90s, the adaptation of the KZpP to the conditions of the market economy with the simultaneous stimulation of the development of democratic principles began. At the same time, the social signifi - cance of labor discipline and disciplinary sanctions for its violation increased again.

Проведен комплексный историко-правовой анализ становления трудового законодательства Украины в сфере правового регулирования дисциплинарной ответственности. Рассмотрены нормативно правовые акты, которые действовали в разные исторические периоды и регулировали вопросы дисциплинарной ответственности работников. Выделены четыре ключевых этапа развития системы правового регулирования соответствующего правового института. Акцентировано внимание на том, что на сегодняшний день развитие трудового законодательства, нормы которого направлены на регулирование дисциплинарной ответственности, не завершено, поэтому этот вопрос является перспективным направлением научных поисков.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; трудове законодавство; labor legislation; трудовое законодательство; правове регулювання; legal regulation; правовое регулирование; дисциплінарна відповідальність; disciplinary responsibility; дисциплинарная ответственность